2006
DOI: 10.1073/pnas.0606810104
|View full text |Cite
|
Sign up to set email alerts
|

Interstrain transfer of the large pathogenicity island (PAPI-1) of Pseudomonas aeruginosa

Abstract: The large Pseudomonas aeruginosa pathogenicity island PAPI-1 of strain PA14 is a cluster of 108 genes that encode a number of virulence features. We demonstrate that, in a subpopulation of cells, PAPI-1 can exist in an extrachromosomal circular form after precise excision from its integration site within the 3 terminus of the tRNA Lys gene. Circular PAPI-1 can reintegrate into either of the two tRNA Lys genes, including the one that was used for integration of small pathogenicity island PAPI-2 in strain PA14. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(167 citation statements)
references
References 32 publications
10
150
0
7
Order By: Relevance
“…Webb et al [14] extracted the replicative-form (RF) DNA of Pf4 (PAO1GI-1) from Pf4-infected cells, and used primers Pf4F and Pf4R to confirm recirculation of prophage Pf4 by the repeat sequence (3′-TGGAGCGGGCGAAGGGAATCGAACCCT-5′). This result was similar to our study, however, we selected a more precise crossing-combining approach of primers [11], and also determined that PAO1GI-1 (prophage Pf4) not only exists in the chromosome, but also can be excised from the chromosome to form a circular intermediate. Mathee et al [21] also found a similar region (RGP5) with PAO1GI-1 ( Table 4) that only determined the excision of RGP5 from the genome.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Webb et al [14] extracted the replicative-form (RF) DNA of Pf4 (PAO1GI-1) from Pf4-infected cells, and used primers Pf4F and Pf4R to confirm recirculation of prophage Pf4 by the repeat sequence (3′-TGGAGCGGGCGAAGGGAATCGAACCCT-5′). This result was similar to our study, however, we selected a more precise crossing-combining approach of primers [11], and also determined that PAO1GI-1 (prophage Pf4) not only exists in the chromosome, but also can be excised from the chromosome to form a circular intermediate. Mathee et al [21] also found a similar region (RGP5) with PAO1GI-1 ( Table 4) that only determined the excision of RGP5 from the genome.…”
Section: Discussionsupporting
confidence: 62%
“…Further, the circular intermediate was not detected by Mathee et al [21] because GIs with unclear boundaries were identified and crossing-combining primers were nonspecific resulting in the inability to produce all four amplification products, including the circular intermediates. PA14GI-4, namely PAPI-1, was also determined similarly [11]. We also designed primers to determine the mobility of PAOGI-2 and Pf0-1GI-1, but our study revealed that these 2 GIs were not deleted from the chromosomes proving that Rve family proteins may not catalyze the excision of GIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acquisition of plasmids and genomic islands has been implicated in epidemic outbreaks, including Pseudomonas aeruginosa, Staphylococcus aureus, and Yersinia spp. [6][7][8]. But in natural settings, we understand little about how bacterial strains vary in their capacity to dominate local sites or host populations or to spread among sites across ecological barriers.…”
Section: Introductionmentioning
confidence: 99%